The effect of honokiol on pulmonary artery endothelium cell autophagy mediated by cyclophilin A in hypoxic pulmonary arterial hypertension - Xiaoying Wang; Dandan Xiao; Cui Ma; Lixin Zhang; Qingya Duan; Xiaodong Zheng; Min Mao; Daling Zhu; Qian Li (Elsevier, 2019)
Abnormal autophagy plays critical roles in the structure and function of the pulmonary vasculature. Cyclophilin A (CyPA) can be secreted from cells in response to hypoxia and oxidative stress, which are involved in inducing autophagy and regulating the function of endothelial cells in pulmonary arterial hypertension. Honokiol is a small molecule natural compound; it has many bioactivities, such as antitumor, anti-inflammatory, antioxidant and antiangiogenic properties, but how honokiol mediates autophagy in pulmonary arterial hypertension is unclear. Rat' lungs gavaged with honokiol were examined for autophagy via western blot and fluorescence microscopy. In addition, western blot, quantitative RT-PCR and immunofluorescence were employed to test the expression of CyPA and autophagy markers in pulmonary artery endothelial cells (PAECs). Small interfering RNA targeting CyPA (si-CyPA) was used to knockdown the expression of CyPA, and then autophagy was tested with mRFP-GFP-LC3 fluorescence microscopy and western blot. We found that honokiol could reduce the expression of CyPA and autophagy markers in vivo and in vitro. Furthermore, autophagy was also down-regulated by si-CyPA. Taken together, we revealed a novel mechanism by which honokiol regulates autophagy. The results revealed that honokiol can alleviate autophagy and pulmonary arterial hypertension regulated by CyPA in PAECs. Keywords: Honokiol, Autophagy, Cyclophilin A, Pulmonary arterial hypertension, Pulmonary artery endothelial cells